Questioning the Independence of Media Coverage in the 2019 Elections - Rudy Iskandar Ichlas (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
This research is motivated by the Television as a news media easily and quickly disseminates information. The formulation of the problem in this study is how to implement the independence of television media coverage of the 2019 Presidential Election? The theory used contains the theory of distributive justice Aristotle (Grand Theory), Election theory (Middle Theory) and Agenda Setting theory Communication (Applied Theory). The research method is empirical normative method with inductive qualitative analysis. The results of this study are the implementation of an independent television media coverage of the 2019 Presidential Election for the 2019 Presidential Election television media proving the existence of a conflicting principle of impartiality. This is not in line with Article 5 letter i of Law Number 32 of 2002 concerning Broadcasting transferred to broadcasting intended to provide balanced information. News which is a product of broadcasting programs in the form of journalistic work becomes a Press dispute is the authority of the Press Council. Juridical coverage of media coverage which is not independent by juridical also opposes because it is not in line with Article 6 letter d of Law Number 40 of 1999 concerning supervising, supervising, correcting, and advising on matters relating to general issues, not the owners of television media the partisan.Keywords: Independence; Television; Elections.